Handbook of adhesives and surface preparation : technology, applications and manufacturing - Ebnesajjad, Sina (PDL handbook series., 2011)
Provides a practical survey of all aspects of adhesives technology, from selection and surface preparation to industrial applications and health and environmental factors. The handbook focuses on the applied aspects of adhesives selection and applications, and it provides practical techniques for rendering materials surfaces adhearable. Particular attention is given to adhesives applications in the automotive, aerospace, medical, dental and electronics sectors.